Inclusion of Cocoa Bean Shell in the Diet of Dairy Goats: Effects on Milk Production Performance and Milk Fatty Acid Profile - Renna, Manuela; Lussiana, Carola; Colonna, Letizia; Malfatto, Vanda Maria; Mimosi, Antonio; Cornale, Paolo (Frontiers in Veterinary Science, 2022)
The use of agro-industrial by-products in animal nutrition is a promising strategy to reduce the food-feed competition, the diet cost at farm level and the environmental impact of animal-derived food production. In this study, the suitability of cocoa bean shell (CBS), a by-product of the cocoa industry, as a feed ingredient in the diet of dairy goats was evaluated, with a focus on the related implications on feed intake, milk yield, milk main constituents, and fatty acid (FA) profile of milk fat. Twenty-two Camosciata delle Alpi goats were divided into two balanced groups. All the goats were fed mixed hay ad libitum. The control group (CTRL; n = 11) also received 1.20 kg/head × day of a commercial concentrate, while in the experimental group (CBS; n = 11) 200 g of the CTRL concentrate were replaced by the same amount of pelleted CBS. The total dry matter intake of the goats was reduced by the dietary inclusion of CBS (P ≤ 0.01). The milk yield, as well as the milk fat, protein, and casein contents and yields were unaffected by the treatment. Milk from the CBS-fed goats showed decreased urea content when compared to the CTRL group (P ≤ 0.001). Milk from the CBS group of goats also showed increased concentrations of total branched-chain FA (both iso and anteiso forms; P ≤ 0.001) and total monounsaturated FA (P ≤ 0.05), as well as a decreased ∑ n6 / ∑ n3 FA ratio (P ≤ 0.05). De novo saturated FA, total polyunsaturated FA, total conjugated linoleic acids, and the majority of ruminal biohydrogenation intermediates remained unaffected by the dietary treatment. These results suggest that CBS can be strategically used as an alternative non-conventional raw material in diets intended for lactating goats, with no detrimental effects on their milk production performance. The use of CBS in goat nutrition may be hindered by the presence of theobromine, a toxic alkaloid. Special attention is needed by nutritionists to avoid exceeding the theobromine limits imposed by the current legislation. Detheobromination treatments are also suggested in literature to prevent toxic phenomena.